In-season resistance training for professional male volleyball players - Cardoso Marques, M. A.; Gonzalez-Badillo, J. J.; Kluka, D. A. (Strength and Conditioning Journal, 2006)
Given this article's focus upon a presumed readership of strength and conditioning coaches, the authors have assumed a familiarity with RT exercises such as bench press, squat, plyometrics, and weightlifting movements. We merely suggest and deploy concepts based on the scientific literature and our professional experience with professional volleyball athletes.